Understanding and teaching Holocaust education - Cowan, Paula; Maitles, Henry (London ; Sage Publications, 2017)
"The Holocaust is a controversial and difficult teaching topic that needs to be approached sensitively and with an awareness of the complex and emotive issues involved. This book offers pragmatic pedagogical and classroom-based guidance for teachers and trainee teachers on how to intelligently teach holocaust education in a meaningful and age-appropriate way." --
Includes bibliographical references (pages 157-175) and index.
Keywords: Holocaust, Jewish (1939-1945) -- Study and teaching; Jews -- Education